Unplanned Healthcare Utilization Following the Surgical Management of Musculoskeletal Tumors: A Retrospective Cohort Study - Devika A. Shenoy; William C. Cruz; Kevin A. Wu; Aaron D. Therien; Malcolm DeBaun; Christian A. Pean; Brian Brigman; Julia D. Visgauss; William C. Eward (Journal of Surgical Oncology, 2026)
ABSTRACT Background and Objectives Orthopaedic oncology patients are susceptible to unplanned return to the emergency department (RTED) and readmission postoperatively. This study aims to explore factors contributing to unplanned healthcare utilization in patients undergoing surgery for musculoskeletal tumors. Methods We conducted a single‐institution retrospective cohort study of orthopaedic oncology patients from 2017 to 2023. Demographic variables (race, ethnicity, language, insurance, age) and procedure details were collected. Multivariable logistic regressions were used to determine the associations between these variables and RTED/readmission. Results Of 1832 orthopaedic oncology patients, 245 (13.4%) had an unplanned RTED and 157 had an unplanned readmission (8.6%) within 90 days. Compared to soft tissue procedures, the odds of 90‐day RTED were significantly higher for spine/pelvis procedures (OR: 2.88, p = 0.003), oncologic fracture (OR: 2.51, p < 0.001), biopsies (OR: 2.51, p < 0.001), and amputations (OR: 2.06, p = 0.03). The same procedures also had higher odds of 90‐day readmission. Medicaid insurance (OR: 2.12, p = 0.008), hypertension (OR: 1.54, p = 0.02), and type 2 diabetes (OR: 1.52, p = 0.04) were associated with higher odds of 90‐day RTED. Conclusions In orthopaedic oncology, patients on Medicaid insurance, patients who undergo high‐risk procedures, and patients with medical comorbidities such as type 2 diabetes and hypertension may be at high risk for adverse outcomes.